2005
DOI: 10.1149/1.1870755
|View full text |Cite
|
Sign up to set email alerts
|

Onset Mechanism of Jahn-Teller Distortion in 4 V LiMn[sub 2]O[sub 4] and Its Suppression by LiM[sub 0.05]Mn[sub 1.95]O[sub 4] (M = Co, Ni) Coating

Abstract: There have been several causes for the capacity fading of LiMn 2 O 4 reported by many authors, which include Mn dissolution into the electrolyte, and the onset of a Jahn-Teller distortion. One of the main remedies suggested to combat those causes has been doping with other transition-metal ions. However, most of the deterioration reactions take place on the LiMn 2 O 4 surface. In this study, LiMn 2 O 4 was coated with a doped-spinel oxide to combat the causes of capacity fading in LiMn 2 O 4 , which modifies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…Various mechanisms have been proposed to explain the capacity fading, including dissolution of Mn cations into electrolyte, Jahn-Teller distortion, and changes in crystallinity [5][6][7]. It was found that doping of metal ions, such as Al [8], Ni [9], Co [10], Cr [11] and Ti [12] ions, into LiMn 2 O 4 spinel can enhance its structural stability, consequently its cyclability can be apparently improved.…”
Section: Introductionmentioning
confidence: 99%
“…Various mechanisms have been proposed to explain the capacity fading, including dissolution of Mn cations into electrolyte, Jahn-Teller distortion, and changes in crystallinity [5][6][7]. It was found that doping of metal ions, such as Al [8], Ni [9], Co [10], Cr [11] and Ti [12] ions, into LiMn 2 O 4 spinel can enhance its structural stability, consequently its cyclability can be apparently improved.…”
Section: Introductionmentioning
confidence: 99%
“…lattice would undoubtedly affect the three-dimensional Li + diffusion pathway, which results in the capacity fade of active materials [6]. Therefore, Jahn-Teller distortion is one of the most important causes of capacity fade of spinel LiMn 2 O 4 [7]. And this phase transition should be suppressed to obtain the excellent cycling performance of active materials.…”
Section: Introductionmentioning
confidence: 99%
“…Many works have been done to study the relationships between the structural properties and electrochemical properties of LiNi x Mn 2 À x O 4 . Our recent work using in situ bending beam method has found that the Ni substitution suppressed the JahnTeller distortion of the [MnO 6 ] octahedron [14]. Wakihara et al [15], have studied the electrochemical and structural properties of Ni substituted LiMn 2 O 4 , and found the Ni substitution gave rise to a more stabled crystal structure than the non-substituted one.…”
Section: Introductionmentioning
confidence: 99%